PENGARUH AKUPRESUR TERHADAP NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Dewi Candra Resmi; Indrawati Aris Tyarini (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Background: Back pain in pregnancy is back pain that occurs in the lumbosacral area. Acupressure or commonly known as totok / finger prick therapy is a form of physiotherapy by giving massage and stimulation at certain points on the body.Objective: To determine the effect of acupressure on low back pain in third trimester mothers.Methods: This study used a Quasy Experiment Design with a nonequivalent pre-test post-test approach. The population was all trimester III pregnant women, with a purposive sampling of 14 pregnant women with low back pain.Results: The results showed the mean level of low back pain in acupressure before treatment was 4.93 ± 2.056, the mean after treatment was 2.64 ± 1.646. Paired Samples Test results obtained p value 0,000 means that there is a decrease in low back pain after treatment so that there is a significant effect of acupressure on low back pain before and after treatment. Conclusion: There is an effect of acupressure on low back pain in third trimester pregnant women with a p value of 0,000.Keywords: Low back pain in pregnant women, Acupressure